A Study of Selected Correlates of Organizational Stress in Higher Education Institutions - Kumari, Nisha; Verma, Shashi; Verma, Yoginder Singh (Prabandhan: Indian Journal of Management, 2012)
In the modern world, stress is a phenomenon that must be seriously recognized and addressed in various professions, particularly in view of increasing incidents of burnouts and health hazards. The teaching profession is no exception. Knowledge about stressors could be valuable in order to avoid and/or manage factors causing stress in teaching at the higher educational level. The present study attempts to understand the relationship of organizational role stress with personal factors such as gender, age and education. The study was conducted among college teachers serving in Himachal Pradesh. After collecting data from representative sample and tabulating it, statistical techniques like Correlation, ANOVA and Regressions were used to analyze the data. The results revealed significant relationship of gender with certain stress dimensions namely, inter role distance, role explosion, role overload and role ambiguity. Males were found to be more under the influence of stress as compared to females. Further, the respondents from the lowest age group and lowest level of education were found to be highly stressed. Teachers at the formative stage tend to be more under stress. The reasons may be varied depending upon the career aspirations, family responsibilities and environmental threats. Since a stressful employee is hardly a productive employee, hence strategies should be worked out for providing an environment where the employees seek solutions for the effective management of their stress.